2018
DOI: 10.1080/10408398.2018.1453779
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inorganic nitrate and nitrite consumption on cognitive function and cerebral blood flow: A systematic review and meta-analysis of randomized clinical trials

Abstract: We conducted a systematic review and meta-analysis of randomized clinical trials examining the effect of inorganic nitrate or nitrite supplementation on cognitive function (CF) and cerebral blood flow (CBF). Two databases (PubMed, Embase) were searched for articles from inception until May 2017. Inclusion criteria were: randomized clinical trials; participants >18 years old; trials comparing a nitrate/nitrite intervention with a control. Thirteen and nine trials were included in the meta-analysis to assess CF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 38 publications
2
36
2
Order By: Relevance
“…In contrast with our results, multiple studies show no significant association with foods containing nitrate and changes in cognitive function or mood [54][55][56][57][58][59][60] . Possible factors contributing to conflicting cognitive responses reports and our own study include different routes of treatment (continual in water vs episodic in meals), different nitrate doses and lengths of treatment, food matrix effects, age and health status of participants, or unidentified species-specific effects.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with our results, multiple studies show no significant association with foods containing nitrate and changes in cognitive function or mood [54][55][56][57][58][59][60] . Possible factors contributing to conflicting cognitive responses reports and our own study include different routes of treatment (continual in water vs episodic in meals), different nitrate doses and lengths of treatment, food matrix effects, age and health status of participants, or unidentified species-specific effects.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, in some areas, the nutrition professionals surveyed were more optimistic about beneficial effects of nitrate than justified by the present state of the knowledge. Over a quarter of participants believed that inorganic nitrate improves cognitive function, despite the lack of consistent evidence to support this notion,33–38 and a recent meta-analysis reporting no overall effect of nitrate on cognition or cerebral blood flow 30. Similarly, almost a quarter of participants claimed that nitrate improved lung function, despite little evidence existing to support this notion 39 40.…”
Section: Discussionmentioning
confidence: 99%
“…Questions where current evidence is ambiguous or where there is no correct response (ie, the answer reflects a belief or opinion on inorganic nitrate) were not included in the Index. Recently published systematic reviews and meta-analyses were used to inform these decisions 17 24 30 31…”
Section: Methodsmentioning
confidence: 99%
“…Current evidence, which is principally derived from observational studies, has identified numerous dietary factors associated with better cognitive performance, with cell and mouse models providing insights into underlying physiological and molecular mechanisms (Vauzour et al 2017; Scarmeas et al 2018). Nutritional compounds which have attracted attention for their potential to improve cognition include the n ‐3 fatty acid, docosahexaenoic acid (DHA) (Dyall 2015), B vitamins (Luchsinger et al 2007; Lefèvre‐Arbogast et al 2016), plant‐derived flavonoids (Commenges et al 2000; Letenneur et al 2007), vitamin D (Anastasiou et al 2014) and, inconsistently, inorganic nitrate (Gilchrist et al 2014; Shannon et al 2017; Clifford et al 2019). However, comprehensive longitudinal data, combining sensitive neural biomarkers ( e.g.…”
Section: Nutrition and Healthy Brain Ageingmentioning
confidence: 99%